An Absurd Concept of Self-Medication: A Case of Oral Chemical Burn - Yagyeshwar Malhotra; Parul Uppal Malhotra; Neera Ohri; Anindita Mallik (International Healthcare Research Journal, 2020)
A chemical burn is seen in oral cavity after a noxious agent is placed in direct contact with the mucosa as a mode of self treatment or iatrogenically by dentist. Mild lesions due to less irritating agents result in mild alteration in texture, while more severe lesions (soreness to outright pain) are due to more irritating agents and because of agents of longer duration of contact. Commonly used chemicals used by patients for tooth pain are aspirin which is placed next to the offending tooth and OTC preparations. The essential oil based preparations are easily available in pharmacies or are prepared by local people. These medicaments can harm a patient if not used under medical or ayurvedic supervision as they have beneficial plant extracts, essential oils etc. A case of such self inflicted chemical burn of the oral mucosa is reported due to use of clove oil preparation available locally, used with varying amount and frequency. History of using over the counter medicaments for dental ailment should be asked when patients visit the dentist with complains of burning or white patch in mouth.